STRATEGIC TRANSFORMATION IN THE AGE OF AI LINKING DIGITAL INNOVATION TO ORGANIZATIONAL EFFECTIVENESS - Ali Abdulhussein Gaber Aljashaam (PT. Antis International Publisher, 2025)
Objective: Artificial Intelligence (AI) is a radically new force that is changing organizational strategies in the rapidly changing digital world, especially in developing economies such as Iraq. The paper examines the connection between the capabilities of AI and digital innovation and organizational performance in the context of Iraqi organizations in the face of infrastructural, economic, and cultural limitations. Basing the study on the Resource-Based View and Dynamic Capabilities Theory, a conceptual model is constructed and operates that the digital innovation by AI is associated with strategic transformation and performance results. Method: The research utilizes Structural Equation Modeling (SEM) in testing its hypotheses through the use of a quantitative cross-sectional study with data provided by 200 organizations. Results: Findings indicate that AI potentials have a great impact on promoting digital innovation, which, consequently, mediates the connection between AI and organizational performance. The results show that digital innovation is a key tool to utilize AI technologies in enhancing strategic agility and performance in the face of a turbulent environment. Novelty: The study does not only fill the existing gaps in empirical research in the Middle East but also provides practical implications to policymakers and managers interested in promoting innovation driven by AI. It has been suggested to invest in AI, become digitally literate, implement smart systems, and have an innovation-oriented organizational culture. Finally, the paper ends with the future research directions, which would help to contextualize the AI integration in the countries with emerging economies even better.